Sri Lanka PPP Diagnostic Note : Accelerating Infrastructure Investment through PPPs - World Bank Group (World Bank, Washington, DC, 2017)
Fiscal constraints and limited budget resources will require the Government of Sri Lanka to explore and consider alternative financing options to address the country’s infrastructure needs. One option to address these constraints is to mobilize private sector financing through the use of Public Private Partnerships (PPPs). However, it is important to note that PPPs have direct and indirect fiscal and financial implications which need to be assessed on a case by case basis and fully understood by participating agencies and policy makers.